PENGGUNAAN MODEL PBL TERINTEGRASI TaRL DAN KSE DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI UNSUR, SENYAWA DAN CAMPURAN - Kurnia Kharismanda; Sunu Kuntjoro; Rahmawati Nur Sandi E. T. P. (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research is Classroom Action Research with the aim of finding out the application of the Problem Based Learning model which integrates the TaRL (Teaching at The Right Level) and KSE (Social Emotional Competence) approaches in improving the learning outcomes of class VIII B students at SMPN Bojonegoro Integrated Model. The research was carried out in two cycles which included planning, action, observation and monitoring and reflection stages. The research subjects were 32 students in class VIII B of Bojonegoro Integrated Model Middle School for the 2023/2024 academic year. The instrument used is a post test. The results showed that there was an increase in student learning outcomes with a completion percentage of 40.63% in cycle 1 and a completion percentage of 78.13% in cycle 2. The learning outcomes of students in groups in each category (very advanced, proficient and developing) also increased. Based on these results, it can be concluded that the use of the PBL model which integrates TaRL and KSE can improve the learning outcomes of students at VIII B SMPN Integrated Model Bojonegoro in elements, compounds and mixtures.